Akibat Hukum Pembatalan Akta Kelahiran Terhadap Anak - Sandjojo, Natasya Immanuela (University of Jember, 2015)
Research on the legal consequences of the cancellation of birth certificates against children aims to know the effect of law affecting the child, as well as a review of the determination and verdict of judges in the court who play a role in legal action cancellation of birth certificate. This research also describes the importance of birth certificate due to the low public awareness to register the birth certificate. Research conducted using normative juridical research, which faces legal issues with the process of discovering legal rules, legal principles, and legal doctrines relating to the issue of law. This study used a deductive method that begins from the things that are common then applied to the formulation of the problem and can produce answers that are specific and legitimate. Based on the results of research, from the various rules of law, doctrine, and judgment and the determination of the court, that the cancellation of the birth certificate carries considerable legal consequences for the child. This resulted in the status and position of the child, in which this study included several examples of determinations and court decisions regarding the cancellation of birth certificates. In addition, the relationship between children and parents connected with alimentation rights will not be interrupted as long as there is evidence of a blood relationship between parent and child. KEYWORDS: Legal Cancellation of Birth Certificate, Birth Certificate, Birth Certificate Cancellation.